School Culture-based Students’ Wellbeing Development from Islamic Education Perspective: A Study in SD Muhammadiyah Ngabean, Sleman - Widodo, Hendro; Venti, Venti; Jailani, Mohammad; Diponegoro, Ahmad Muhammad (Psikopedagogia, 2022)
This qualitative study aimed to 1) Describe students’ well-being in SD Muhammadiyah, Sleman, and 2) find out the role of school culture in students’ well-being at SD Muhammdiyah Ngabean, Sleman.   Participants were the school principal, teachers, and students. Data were collected through interviews, observation, and documentation and analyzed through three stages: data reduction, data display, and verification. This study found that 1) aspects of student well-being, i.e., self-optimization and satisfaction, were categorized as high, while other aspects i.e., positivity and resilience, were categorized as moderate. 2) School culture that affects students’ well-being include physical artifacts, cooperation, commitment to achievement, harmonious relationship, and reinforcement. Students’ well-being development in SD Ngabean Sleman was relevant to Islamic education and learning patterns. This study may serve as the foundation for developing student’s well-being through school culture.